2021
DOI: 10.1186/s13256-021-03137-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct electrical stimulation for hand function in a stroke patient with severe upper limb paralysis due to lenticulostriate artery occlusion: a case report

Abstract: Background Transcranial direct current stimulation, a therapeutic modality to modulate the excitability of injured and uninjured brain hemispheres in stroke patients, is expected to be effective in treating upper limb paralysis. We describe the use of transcranial direct current stimulation to improve the function and frequency of use of the paralyzed hand of a patient with lenticulostriate artery occlusion. Case presentation A Japanese man in his … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Cerebral infarction, also known as cerebral arterial thrombosis, mostly occurs in middle-aged and elderly people, and its main physiological and pathological process is that the patients suffer from ischemic-hypoxic necrosis of local cerebral tissues on the basis of atherosclerosis and successive neurological impairment and deficit [ 1 ]. According to the epidemiological survey data of stroke in 2013, the incidence and mortality of cerebral infarction in China were much higher than the world average level, and its incidence reached up to 42% among Chinese men and 37% among Chinese women [ 2 ]. In 2019, the Lancet further confirmed that the cerebral stroke was the primary cause of death in China from 1990 to 2017 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral infarction, also known as cerebral arterial thrombosis, mostly occurs in middle-aged and elderly people, and its main physiological and pathological process is that the patients suffer from ischemic-hypoxic necrosis of local cerebral tissues on the basis of atherosclerosis and successive neurological impairment and deficit [ 1 ]. According to the epidemiological survey data of stroke in 2013, the incidence and mortality of cerebral infarction in China were much higher than the world average level, and its incidence reached up to 42% among Chinese men and 37% among Chinese women [ 2 ]. In 2019, the Lancet further confirmed that the cerebral stroke was the primary cause of death in China from 1990 to 2017 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%